Rancang Bangun Sistem Pemesanan Menu Berbasis Web Menggunakan QR-Code Dan Midtrans Web Service Sebagai Payment Gateway (Studi Kasus: Kedai Kopi Bang Ar) - Satria Ade Putra (CV. Multi Kreasi Media, 2024)
At present the development of technology is so rapid with the presence of new devices that can facilitate use in the culinary business world which focuses on coffee shops or restaurant., Recording and processing of menu data, menu quantities and prices, as well as ordering transaction data is still done manually, namely by recording on the paper. The difficulty in recording and calculating the number of types of menus, the number of menus, and the size of the total price resulted in the data not being obtained in real time. To improve the accuracy of the data, it is necessary to develop a computerized menu ordering information system. Research in actual circumstances will be a full supporting tool for serving coffee shop or restaurant menus. To create a new system model, a system development process is needed to build the system in detail based on the results of the analysis of the existing system. The process required in utilizing the waterfall technique to build an application according to specifications. Implementing the QR code technology feature as a substitute for the menu list at every coffee shop dining table. So that when a customer arrives, the waiter does not need to provide a menu list anymore, the customer only needs to scan the QR code on the table. In addition, the payment transaction process along with the development of its special technology in the case of non-cash payment transactions or Fintech (Financial Technology) which should be applied to the payment transaction process, it is from this that researchers make developments regarding how to order menus which can later help buyers who will order food or drinks. Based on the results of research on making a menu ordering system, an application is produced that is able to help employees serve customers well. That is, the menu ordering process is carried out with the customer's smartphone with an easy-to-understand web display, making it easier to order menus for both customers and employees and also Midtrans webservice as a payment gateway can make it easier for customers to process transactions, because non-cash payments can be made by various banks. or a digital wallet and sales data storage stored in real time into the database so that employees do not need to record sales data back into the sales report book.